2019
DOI: 10.3847/1538-4357/aaf79f
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry in Hot H2-dominated Exoplanet Atmospheres

Abstract: Photochemistry has the potential to substantially impact the atmospheric composition of exoplanets with consequences on the radiative transfer, thermal structure and dynamics of the atmospheres, particularly in UV-rich stellar environments. Here, we present the results of a first laboratory experimental simulation of photochemistry in carbon-rich exoplanet atmospheres at elevated temperatures. Evolution of gas-phase molecular composition was quantitatively monitored with infrared spectroscopy and mass spectrom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
154
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(173 citation statements)
references
References 71 publications
(91 reference statements)
14
154
5
Order By: Relevance
“…Common organic molecules are not stable at very high temperature (>1000 K, Johns et al 1962, Smay 1985, so we would not necessarily expect significant organic haze in the atmospheres of Jupiters hotter than 1000 K. This is consistent with a recent modeling study (Gao et al 2020), which found that aerosol composition is dominated by silicates for hot giant exoplanets with planetary equilibrium temperatures above 950 K, while is dominated by hydrocarbon aerosols below 950 K. However, it is possible to form organic hazes at temperatures above 1000 K as reported by Fleury et al (2019) who found that photochemistry can lead to the formation of an organic solid condensate at 1500K. We also need to consider that temperatures on the night sides of these hot planets can be significantly lower than on the day side, so there may be situations where gases that are photochemically produced on the day side are transported by winds to the night side, where they can form condensates.…”
Section: Haze Production Ratesupporting
confidence: 90%
See 2 more Smart Citations
“…Common organic molecules are not stable at very high temperature (>1000 K, Johns et al 1962, Smay 1985, so we would not necessarily expect significant organic haze in the atmospheres of Jupiters hotter than 1000 K. This is consistent with a recent modeling study (Gao et al 2020), which found that aerosol composition is dominated by silicates for hot giant exoplanets with planetary equilibrium temperatures above 950 K, while is dominated by hydrocarbon aerosols below 950 K. However, it is possible to form organic hazes at temperatures above 1000 K as reported by Fleury et al (2019) who found that photochemistry can lead to the formation of an organic solid condensate at 1500K. We also need to consider that temperatures on the night sides of these hot planets can be significantly lower than on the day side, so there may be situations where gases that are photochemically produced on the day side are transported by winds to the night side, where they can form condensates.…”
Section: Haze Production Ratesupporting
confidence: 90%
“…The higher production rate without CH4 indicates that CH4 is neither required to generate organic hazes nor necessary to promote the organic haze formation. CO and/or CO2 can serve as a carbon source for haze formation (Fleury et al 2017(Fleury et al , 2019He et al 2018aHe et al , 2018bHe et al , 2019He et al , 2020Hörst et al 2018b;Moran et al 2020).…”
Section: Haze Production Ratementioning
confidence: 99%
See 1 more Smart Citation
“…However, since all the observed planets do not have large methane concentrations, other pathways might be more important. Particularly, recent experiments at ≈ 1500 K by (Fleury et al 2019) have shown that photochemical hazes can form in a pure H2-CO gas at high temperature. Haze and condensation clouds are expected to be affected differently by the atmospheric circulation.…”
Section: Hazementioning
confidence: 99%
“…Critically, exoplanet aerosol experiments have demonstrated that methane, long used in the exoplanet literature as an essential component of haze formation (e.g. Morley et al, 2015;Kawashima & Ikoma, 2018;Gao et al, 2020), is not always needed to produce substantial amounts of haze (Hörst et al, 2018;He et al, 2018b;Fleury et al, 2019;He et al, 2020bHe et al, , 2020a and that exoplanet hazes likely contain more than just hy- Figure 10. Laboratory hazes made from hydrogen-rich, water-rich, and carbon dioxide-rich atmospheres from 300 K to 600 K have a range of colors at visible wavelengths, some unlike those seen in solar system hazes (He et al, 2018a).…”
mentioning
confidence: 99%